Brain-wide cellular resolution imaging of Cre transgenic zebrafish lines for functional circuit-mapping - Kathryn M Tabor; Gregory D Marquart; Christopher Hurt; Trevor S Smith; Alexandra K Geoca; Ashwin A Bhandiwad; Abhignya Subedi; Jennifer L Sinclair; Hannah M Rose; Nicholas F Polys; Harold A Burgess (eLife, 2019)
Decoding the functional connectivity of the nervous system is facilitated by transgenic methods that express a genetically encoded reporter or effector in specific neurons; however, most transgenic lines show broad spatiotemporal and cell-type expression. Increased specificity can be achieved using intersectional genetic methods which restrict reporter expression to cells that co-express multiple drivers, such as Gal4 and Cre. To facilitate intersectional targeting in zebrafish, we have generated more than 50 new Cre lines, and co-registered brain expression images with the Zebrafish Brain Browser, a cellular resolution atlas of 264 transgenic lines. Lines labeling neurons of interest can be identified using a web-browser to perform a 3D spatial search (zbbrowser.com). This resource facilitates the design of intersectional genetic experiments and will advance a wide range of precision circuit-mapping studies.